Why is the Diagnostic and Statistical Manual of Mental Disorders so hard to revise? Path-dependence and "lock-in" in classification. (June 2015) - Cooper, Rachel
Abstract: The latest edition of the Diagnostic and Statistical Manual of Mental Disorders, the D.S.M.-5, was published in May 2013. In the lead up to publication, radical changes to the classification were anticipated; there was widespread dissatisfaction with the previous edition and it was accepted that a "paradigm shift" might be required. In the end, however, and despite huge efforts at revision, the published D.S.M.-5 differs far less than originally envisaged from its predecessor. This paper considers why it is that revising the D.S.M. has become so difficult. The D.S.M. is such an important classification that this question is worth asking in its own right. The case of the D.S.M. can also serve as a study for considering stasis in classification more broadly; why and how can classifications become resistant to change? I suggest that classifications like the D.S.M. can be thought of as forming part of the infrastructure of science, and have much in common with material infrastructure. In particular, as with material technologies, it is possible for "path dependent" development to cause a sub-optimal classification to become "locked in" and hard to replace. Highlights: Despite commitment to radical revision, D.S.M.-5 differs little from its predecessor. As the D.S.M.-5 is agreed to be sub-optimal this will hold back research. Path-dependence has led to the classification becoming "locked-in". "Lock-in" is time-dependent and agent-relative and may be overcome in the future.